2014
DOI: 10.2527/jas.2014-7375
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genomic breeding values for residual feed intake in a multibreed cattle population1

Abstract: Residual feed intake (RFI) is a measure of the efficiency of animals in feed utilization. The accuracies of GEBV for RFI could be improved by increasing the size of the reference population. Combining RFI records of different breeds is a way to do that. The aims of this study were to 1) develop a method for calculating GEBV in a multibreed population and 2) improve the accuracies of GEBV by using SNP associated with RFI. An alternative method for calculating accuracies of GEBV using genomic BLUP (GBLUP) equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 30 publications
(48 reference statements)
3
40
0
Order By: Relevance
“…The finding of Khansefid et al . () is consistent with this finding. They used BLUP for genomic selection of residual feed intake and found half the variance was due to SNPs and half due to SNP by breed interactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The finding of Khansefid et al . () is consistent with this finding. They used BLUP for genomic selection of residual feed intake and found half the variance was due to SNPs and half due to SNP by breed interactions.…”
Section: Discussionsupporting
confidence: 92%
“…BAYESR may utilize a number of SNPs to predict the effect of the QTL, and this combination may work in Holsteins but is misleading in Jerseys. The finding of Khansefid et al (2014) is consistent with this finding. They used BLUP for genomic selection of residual feed intake and found half the variance was due to SNPs and half due to SNP by breed interactions.…”
Section: Discussionsupporting
confidence: 91%
“…Variants with effects in the same direction in both breeds resulted in increased across-breed reliabilities of genomic predictions and high genomic correlations, while variants with opposite effects decreased reliabilities and resulted in negative genomic correlations. By fitting separate within- and multi-breed genomic relationship matrices, Khansefid et al [36] reported increases in accuracy for some traits compared to a model using only within-breed relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Four subsets were used as training populations (≈946) and the fifth subset as a validation sample (≈237). The animals for the various subsets were selected randomly, except that paternal half-sibs were always placed in the same subset [42]. Cross-validation was replicated 10 times.…”
Section: Methodsmentioning
confidence: 99%